Rethinking disability empowerment:Inclusive communication management in arts-based social entrepreneurship - Mukhlisiana, Lusy; Ramadhanisa, Nayla; Nabila, Khansa Dei; Firdaus, Indi Aires (Bricolage : Jurnal Magister Ilmu Komunikasi, 2026)
Indonesia’s 22.5 million persons with disabilities face multilayered exclusion, such as physical, communicative, attitudinal, and systemic, resulting in low labor force participation (49,2%). While social entrepreneurship has emerged as a strategic mechanism for inclusive participation, the specific role of communication management in art-based disability empowerment remains underexplored, creating a critical gap between theory and practice. A qualitative multiple case study was conducted at two Bandung-based social enterprises. Tab Space (technology-oriented, providing platforms for artists with disabilities) and PUKA (culturally-oriented, adapting traditional Sundanese arts for diverse disabilities), from February to July 2025. Data were collected through in-depth interviews, participatory observations, and focus group discussions with 10 informants. Data analysis was done using thematic analysis with the help of NVIVO 15 software. Analysis identified two core dimensions: Brand Awareness (175 coding references), dominated by Brand Recognition (39%) and Brand Recall (34%); and Communication Management (98 coding references), led by Interpersonal Communication (36%) and Competence (25%). PUKA employs a “product-first” strategy, while Tab Space adopts a “personal-adaptive” approach. Multi-level challenges were identified, spanning microsystem emotional dynamics to macrosystem cultural stigma. The study introduces the Integrated Model of Inclusive Communication for Social Entrepreneurship (IMCSE), synthesizing asset-based communication, multi-level engagement strategies, and a paradigm shift from charity-based to rights-based communication, social entrepreneurship theory, and disability studies within the Indonesian art context. IMCSE recognizes people with disabilities as equal partners in the inclusive social entrepreneurship ecosystem.